2008
DOI: 10.1289/ehp.11425
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Serum Concentrations of Persistent Organic Pollutants with the Prevalence of Periodontal Disease and Subpopulations of White Blood Cells

Abstract: BackgroundPersistent organic pollutants (POPs), which are endocrine disruptors that accumulate in adipose tissue, can increase the risk of periodontal disease through the disturbance of the immune system.ObjectiveWe examined associations of background exposure to POPs with periodontal disease in the general population.DesignCross-sectional associations of concentrations of serum POPs with the prevalence of periodontal disease were investigated in 1,234 adults ≥ 20 years of age in the National Health and Nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…A joint effect of higher exposures of DDT and PCBs on CD16 + NK cells was also observed in Japanese infants [22]. Finally, neutrophil counts were inversely related to OC pesticides concentrations in the general U.S. population form NHANES 1999-2002 [48]. Similar findings have also been reported in animal and in vitro studies [49-52].…”
Section: Discussionsupporting
confidence: 59%
“…A joint effect of higher exposures of DDT and PCBs on CD16 + NK cells was also observed in Japanese infants [22]. Finally, neutrophil counts were inversely related to OC pesticides concentrations in the general U.S. population form NHANES 1999-2002 [48]. Similar findings have also been reported in animal and in vitro studies [49-52].…”
Section: Discussionsupporting
confidence: 59%
“…POPs exposures have been associated with type 2 diabetes (Zeliger, 2013; Lee et al , 2010; Carpenter 2008); immunological disorders (Hertz-Picciotto et al , 2008; Noakes et al , 2006; Tryphonas, 1998), musculoskeletal disorders (Lee et al , 2007), reproductive interferences (EPA, 2008; Nishijo et al , 2008; Herz-Picciotto et al , 2008), endocrine disruption (Snyder & Mulder, 2001; Colborn et al , 1997), periodontal disease (Lee et al , 2008), neurological disease (Kodavanti, 2005; Patri et al , 2009; Gamble, 2000; White & Proctor, 1997; Burbacher, 1993), neurodevelopmental disorders (Grandjean & Landrigan, 2006; Polanska et al , 2012; Korrich & Sagiv, 2008; Yolton et al , 2011;) and neurodegenerative diseases, including ALS, Alzheimer's and Parkinson's diseases (Parron et al , 2011; Loane et al , 2013; Chen et al , 2013; Steenland et al , 2012; Wang et al , 2011; Dardiotis et al , 2013; Caudle et al , 2012; Weisskopf et al , 2010; Moulton & Yang, 2012; Mayeux & Stern, 2012; Zaganas et al , 2013; Sienko et al , 1990; Vincenti et al , 2012). The onset of many different cancers has been associated with exposures to the chemicals described here.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, inclusion of nonhealthy individuals is acceptable, and in fact, exclusion of such individuals would introduce bias into the results. [45][46][47] Persistent organochlorine pollutants have an immunomodulatory effect in many mammalian species, 48 and a recent study 49 revealed that such persistent organochlorine pollutants are inversely correlated with neutrophil counts in humans. 8,10 Some distributional differences were evident among geographic sites in the present study.…”
Section: Discussionmentioning
confidence: 99%